2017
DOI: 10.1007/s10654-017-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the 2015 Dutch dietary guidelines and risk of non-communicable diseases and mortality in the Rotterdam Study

Abstract: We aimed to evaluate the criterion validity of the 2015 food-based Dutch dietary guidelines, which were formulated based on evidence on the relation between diet and major chronic diseases. We studied 9701 participants of the Rotterdam Study, a population-based prospective cohort in individuals aged 45 years and over [median 64.1 years (95%-range 49.0-82.8)]. Dietary intake was assessed at baseline with a food-frequency questionnaire. For all participants, we examined adherence (yes/no) to fourteen items of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 35 publications
3
125
2
1
Order By: Relevance
“…Direct evidence on adherence to the DHD15-index and incident chronic diseases is still limited, with only one earlier study showing that high adherence to DHD15-index was associated with a lower risk of mortality [10]. Another study investigated the association between adherence to the Dutch guidelines 2015 and 10 chronic diseases in the Rotterdam Study, but did not use the DHD15-index [11]. This study showed that higher adherence to the Dutch dietary guidelines of 2015 was associated with a lower risk of mortality, stroke, chronic obstructive pulmonary disease, colorectal cancer, and depression, but not with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Direct evidence on adherence to the DHD15-index and incident chronic diseases is still limited, with only one earlier study showing that high adherence to DHD15-index was associated with a lower risk of mortality [10]. Another study investigated the association between adherence to the Dutch guidelines 2015 and 10 chronic diseases in the Rotterdam Study, but did not use the DHD15-index [11]. This study showed that higher adherence to the Dutch dietary guidelines of 2015 was associated with a lower risk of mortality, stroke, chronic obstructive pulmonary disease, colorectal cancer, and depression, but not with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Previous prospective studies examining dietary patterns and the risk of developing COPD have focused on either prudent/healthy or Western diets (9,10,28,29). In these studies, a prudent/healthy diet lowered the risk of developing COPD, whereas a Western diet increased the risk.…”
Section: Discussionmentioning
confidence: 99%
“…While eligible for inclusion in our review, OGUNMOROTI et al [18] and VOORTMAN et al [38] were not included in this meta-analysis as there were insufficient data provided to calculate odds ratios or RRs based on the HR. OGUNMOROTI et al [18] reported that the ideal diet according to the AHA was not significantly associated with new-onset of COPD compared to a poor diet (HR 0.44, 95% CI 0.06-3.21), while VOORTMAN et al [38] demonstrated that following the Dutch dietary guidelines was associated with reduced COPD (HR 0.94, 95% CI 0.91-0.98).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%